EP976 The impact of extent of cytoreductive surgery (CRS) on epithelial ovarian cancer (EOC), primary peritoneal carcinomatosis(PPC), and fallopian tube cancer (FTC) at the american university of beirut (AUBMC). (1st November 2019) - Seoud, M; El Housheimi, A; Jaafar, I; Hamed, K; Jamali, F; Abdallah, R; Khalil, A
Abstract : Introduction/Background: To study the impact of the extent of CRS [complete Debulking (CD), optimal Debulking (OD) ≤1 cm, or suboptimal Debulking (SOD) >1 cm residual disease] on progression free (PFS) and overall survival (OS) in advanced EOC who underwent primary debulking (PDS) or interval debulking surgery (IDS) between 1998–2018 at AUBMC. Methodology: A retrospective review of the impact of extent of CRS on PFS and OS. Results of 300 patients with EOC, PPC and FTC, 220 were found to have advanced epithelial cancer (stage IIIB, IIIC and IV). 66.4% had CD, 29.7% OD and 2.6% SOD. Results are shown in tables 1 (Pic 1) and 2 and 3 (Pic 2). Median survival is expressed in months. Conclusion: The extent of the cytoreductive surgery significantly prolonged PFS but not OS in stage IIIC but not IV. However this increase in PFS is only seen in the interval setting. Patients who undergo CD have similar PFS and OS regardless of the timing of CRS. Disclosure: Nothing to disclose.